Perencanaan Pengembangan Wisata Desa Edelweis Berbasis Masyarakat (Studi pada Balai Besar Taman Nasional Bromo Tengger Semeru) - Wiyanto, Tri (Jurnal Ilmiah Administrasi Publik, 2020)
One of the efforts of the Bromo Tengger Semeru National Park (BTSNP) Office for conservation Edelweiss, which is through community-based Edelweiss village tourism development. The purpose of this research are to analyze the planning, supporting and restricting factors of community-based Edelweis village tourism development at BTSNP Office. This research is a qualitative descriptive study. The results showed that the top down planning went well enough. While the bottom up planning shows that community participation has not been maximized. Supporting factors include Edelweis' needs by the Wonokitri and Ngadisari Village people, leadership policies, and funding support from BTSNP Office and Bank Indonesia Corporate Social Responsibility. While the restricting factors include awareness and motivation of the Wonokitri and Ngadisari Village people were relatively lacking, unavailability of functional planner at BTSNP Office, unavailability planning support in the RPJMD of Pasuruan and Probolinggo Regency Government, and existence of sectoral egos and management priority differences.